2020
DOI: 10.1159/000507764
|View full text |Cite
|
Sign up to set email alerts
|

The Demand for Hospital Emergency Services: Trends during the First Month of COVID-19 Response

Abstract: Introduction: Since December 2019, more than 925,000 cases of COVID-19 have been reported worldwide, 8,251 cases in Portugal by the end of March. Previous studies related to the SARS pandemic showed a decrease up to 80% in the emergency care episodes. Hence, the objective of this study is to analyze the use of emergency services during the first pandemic month, compared to historical records. Methods: Data from emergency episodes in mainland Portugal, from January 2014 to March 2020, were downloaded from the N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
63
0
5

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 68 publications
(74 citation statements)
references
References 14 publications
3
63
0
5
Order By: Relevance
“…[25][26][27] Investigators have previously raised concern regarding patients potentially avoiding the ED during pandemics because of fear of contracting infectious disease. [11][12][13][14][15][26][27][28][29] Paradoxically, the opposite effect has been observed with other epidemics of respiratory infectious diseases including the 1993 hantavirus epidemic (in New Mexico, Arizona and Colorado) and the 2009 H1N1 influenza pandemic in which ED visits…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[25][26][27] Investigators have previously raised concern regarding patients potentially avoiding the ED during pandemics because of fear of contracting infectious disease. [11][12][13][14][15][26][27][28][29] Paradoxically, the opposite effect has been observed with other epidemics of respiratory infectious diseases including the 1993 hantavirus epidemic (in New Mexico, Arizona and Colorado) and the 2009 H1N1 influenza pandemic in which ED visits…”
Section: Discussionmentioning
confidence: 99%
“…9 Many physicians and hospitals have reported a reduction in ED visits and hospital admissions for acute illness since the onset of the COVID-19 pandemic. [10][11][12][13][14][15] There are, however, few to no data comparing the effects of COVID-19 on the diagnosis of illnesses of different urgency on imaging. Furthermore, the effects of the COVID-19 pandemic on the diagnosis of many acute illnesses have not been independently assessed.…”
Section: Researchmentioning
confidence: 99%
“…Most radiologists at our department perceived an associated decrease in the computed tomography (CT) studies of the head ordered through the emergency department (ED) since the first case was identified in Hamilton. A substantial decrease in the daily ED visits since the pandemic has been confirmed at other institutions by multiple recent studies all over the globe [4][5][6][7][8][9][10][11]. Bres Bullrich et al found a 20% decrease in the number of code strokes in the beginning of the pandemic compared with that in a similar period 1 year prior [11].…”
Section: Introductionmentioning
confidence: 91%
“…Many hospitals have reported a roughly 50% decrease in emergency room visits. 8 A study published in the American College of Cardiology in April 2020 reported a 38% drop in patients being treated for myocardial infarction. 9 As the prevalence of these conditions has not decreased, it is thought that patients may be avoiding medical care out of fear of COVID-19 exposure should they go to the hospital.…”
Section: Discussionmentioning
confidence: 99%